PENGARUH STRATEGI PDEODE (PREDICT-DISCUSS-EXPLAIN- OBSERVE-DISCUSS-EXPLAIN) TERHADAP PENGUASAAN KONSEP SISWA PADA MATERI ORGANISASI KEHIDUPAN - Sri Wulan Siti Fatimah; Agus Martono; Hadiansah Hadiansah (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2015)
The concept of organizational life in a biology lesson material that requires understanding quite difficult. There fore we need aninnovation that makes student learning is not saturated in an easy to learn and understand a concept PDEODE one of them with a strategy that could potentially broaden and deepen students' conceptual knowledge. The purpose of this study is to determine the effect of the strategy PDEODE student mastery of concepts in the material organization of life.This study departs from the idea that learning the material organization of life with perceived PDEODE strategy would cor respond to the material characteristics of the organization as a strategy PDEODE life is real, it can arouse the curiosity of students, and kontruktivistik so that students can form their own understanding. Through learning by using PDEODE strategy is expected to improve the mastery of student concepts. In this study using Quasi-Experiments with the study population was all students of class VII SMP 1 Atap Cikawao three years of academic classes 2013/2014 and samples in this study were taken two classes with sampling technique used purposive sampling because the research erdiscretion. The instrument used was a test, observation sheets and questionnaires. Test data were analyzed using t-test at the beginning of the test and the Mann-Whitney test at the end of the test and the N-gain. The results obtained on the students mastery of the concept of the experimental class 82.17 and N-gain of 0.72 with high qualifications. Mean while, students mastery of concept son the control class 73.83 and 0.58 with N-gain qualifications being. Mann-Whitney test results obtained on the posttest Zhitung 29 > Ztabel 1.96 and Mann-Whitney test results on the N-gain obtained Zhitung 6.3 > Ztabel 1.96 thus Ho is rejected and Ha accepted. It is proved that there are significant PDEODE strategy on the concept of student mastery of the material organization of life. This is supported by the percentage of adherence to activity by 95.85% teachers with excellent qualifications, student activity by 88% with excellent qualifications and the percentage of student responses at 81% with very strong qualifications.